Why Do Only Some People Blow the Whistle? A Multi-Theoretical Perspective - Edirisinghe, C.; Kailasapathy, Pavithra (My University, 2021)
De George’s Theory of Whistle-blowing explains an individual’s whistle- ϐ Ǥ ǡ it does not adequately explain why only some people blow the whistle. This theoretical paper proposes a framework combining the theories of Principled Organizational Dissent, Resource Dependency, and Moral Conation to address the theoretical gaps in De George’s Theory of Whistle- Ǥ ǡ ϐ mediate the relationships between personal principles, personal cost of reporting, personal responsibility for reporting, evidence of wrongdoing and whistle-blowing intention. Further, based on the Theory of Moral Conation, this paper suggests that the moral conation capacities of ǡ ϐ ǡ ϐ Ǧ Ǥ The main theoretical contribution of the paper is that it addresses three theoretical gaps inherent in De George’s Theory of Whistle-blowing. The proposed framework’s managerial implications include establishing a supportive culture for implementing human resource management systems which promote individual whistle-blowing behaviour. In addition, this study opens up avenues for future research to use morality as a key concept in studies related to whistle-blowing.
Keywords: Whistle-blowing intention; Personal cost of reporting; Personal responsibility for reporting; Evidence of wrongdoing